Coexistence of Helicobacter pylori and Giardia duodenalis causes severe iron deficiency anaemia in an adult male: a case report - Ali Abdelfattah; Nawal S Hijjawi; Khaldun Jacoub (Journal of Infection in Developing Countries)
Introduction: Iron deficiency anaemia (IDA), the most prevalent type of anaemia, is recognised as a significant global health concern that affects individuals of all ages.